2010
DOI: 10.1016/s1658-3876(10)50020-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic effect of hormone receptor status in early HER2 positive breast cancer patients

Abstract: Patients with (HER2+/ HR-) breast cancers treated with surgery and standard adjuvant chemotherapy exhibited a statistically worse DFS compared to those with (HER2+/ HR+) tumors. However, OS was similar in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…[ 25 ] showed that among metastatic breast cancer patients who were HER2+, more HR– patients benefited from trastuzumab treatment compared to HR+ patients. Our finding of greater OS for patients with HR+ status is consistent with several recent reports of various patient subsets [ 7 10 , 25 ]. Although HR+ status was favorable in comparison to HR– status according to univariate analysis, there was no significant difference in multivariate Cox proportional hazards regression analysis.…”
Section: Discussionsupporting
confidence: 93%
“…[ 25 ] showed that among metastatic breast cancer patients who were HER2+, more HR– patients benefited from trastuzumab treatment compared to HR+ patients. Our finding of greater OS for patients with HR+ status is consistent with several recent reports of various patient subsets [ 7 10 , 25 ]. Although HR+ status was favorable in comparison to HR– status according to univariate analysis, there was no significant difference in multivariate Cox proportional hazards regression analysis.…”
Section: Discussionsupporting
confidence: 93%
“…Variability in HR and HER2 results between institutions is an important issue and undefined criteria or variable cutoff values have been used in previous imaging studies on breast cancer subtypes (13). In our study, however, HR and HER2 positivity were defined according to the American Society of Clinical Oncology/College of American Pathologists guidelines (19,20) and our HR+ rate of 50.4% within HER2+ cancer was similar to rates of other studies (50–51.8%) (26,27). Second, the inter-observer variability in image interpretation was not assessed in this study.…”
Section: Discussionsupporting
confidence: 84%
“…Although the 5‐year survival rate of BC is 90%, this disease remains the second most common cause of cancer‐related death, surpassed only by lung cancer in the United States. BC patients with ER‐positive or HER2‐positve disease have poor prognosis because of a high incidence of recurrence, metastasis, and resistance to current treatment modalities . Therefore, there is a need to identify therapeutic agents to combat the disease.…”
Section: Discussionmentioning
confidence: 99%
“…As compared to control, because of a high incidence of recurrence, metastasis, and resistance to current treatment modalities. 40 Therefore, there is a need to identify therapeutic agents to combat the disease. In this study, we investigated the ability of 2HF, natural bioactive product present in citrus fruits, in inhibiting BC growth in vitro and in vivo.…”
Section: Hf Inhibits Growth Of Tumors In Xenograft Mouse Models Ofmentioning
confidence: 99%